(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
Ruling on a vast territory in Aosta Valley, the Challant have long been both dangerous local opponents and active political collaborators of the County (Duchy since the 1416) of Savoy. Since they joined the administration of the County in the early 14th century, they were able to learn how to manage the castellanie (the ‘cells’ of the territorial organization of that area). Through their agents, the local castellans, the Challant governed their domains by requesting precise accounting statements from their officers. The accounting records preserved, together with the franchigie granted by the lords to the rural communities, allow us to meditate on the profitability of these castellanie, but also to assess the strength of the lordship by looking at the seigneurial levies. The analysis shows that the profitability of the Challant lordship was slightly dependent on the wealth of direct income; on the contrary, the possession of castles had a decisive political role in conveying the image of power of the lords.